B3 Waste Management at PT Kereta Api Indonesia: a Literature Review - Dewi, Dewi Fortuna Khairil; Razak, Abdul; Handayuni, Linda; Yuniarti, Elsa (Jurnal Ilmiah Platax, 2024)
The amount of B3 waste sourced from the Locomotive Depot, Station, and Balai Yasa office of PT Kereta Api Indonesia (Persero) which is not managed properly and correctly will cause problems later both for the surrounding environment, passengers, and water quality that is close to the location of the waste source. This study aims to determine the management of B3 Waste carried out at all PT Kereta Api Indonesia stations. This type of research is research using the literature review method. The stages of literature collection used in this study refer to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. This stage has four procedures: identification, screening, eligibility, and acceptance. This study shows that the management of hazardous waste at several stations from the articles that have been reviewed is found to be inconsistent with the workmanship and management based on applicable regulations. It can be concluded that hazardous waste at some of these stations does not meet the grouping, storage, and management requirements.